Community Support for Disabled Bus Riders: What Can We Do? - Kawaguchi, A.; Chiu Chan (International Conference of Computing in Engineering, Science and Information, 2009)
This paper discusses the implementation of one type of information systems for the New York City bus transit service, as a case study to provide value-added transportation services for the people in need of mobile wheelchairs. Information technology is a key for finding out flexible transportation services especially for disabled people. Useful information supplies psychological reassurance to these vulnerable people to make them feel more safe and secure. Residents in metropolitan areas increasingly view the convenience of public transportation, and they are becoming used to supply and retrieve the information gathered for regional community. The accessibility improvement needs the exact same type of the cooperation of transportation companies and regional residents. The widespread use of mobile wheelchairs has a socioeconomic impact. The significance of this research for the longer-term goals lies in its implications for adaptation of this kind of intelligent models into the future welfare activities.